No cell for the soul: prison, philosophy and Bernard Stiegler : a short appreciation - Earle, Rod (Journal of Prison Education and Reentry, 2021)
Bernard Stiegler was a French philosopher who served 5 years in prison for a series of bank robberies committed in his youth. He died in August 2020, aged just 68, a professor celebrated in the highest ranks of continental philosophy. Stiegler subsequently published over 30 books, at the core of which is the series tellingly gathered under the title ‘Time and Technics’. His essay, ‘How I became a Philosopher’, convinced me he, and it, should be on every prison philosophy course. In this article I outline why, as a convict criminologist, I feel an affinity with Stiegler’s project.